Solvent Surface Tension Effect on Passive Liquid Q – switch Pulse Duration - Abdul-Munim l-Kamil (University of Thi-Qar Journal of Science, 2019)
Nickel dye, Bis-(4-Dimethylaminodithobenzil)-Nickel (BDN-I) was used as liquid Q-switch for Nd: YAG laser. Solvent surface tension effect on the Q-switched pulse duration was investigated. Carbon tetrachloride (CCl4), Chloroform (CHCl3), and dioxin (C4H8O) were used as solvents to BDN-I at molar concentration of 59.52 M/l. The measured Qswitched pulse duration was 60± 2.33, 71± 1.95, and 84± 1.32 nsec respectively. The greatest pulse duration reduction was achieved by using CCl42which is of the lowest surface tension with respect to other olvents. The study related that to the low ability of electron transfer from this solvent to the dye molecules. Key words: Physics, Laser, Passive Q-switching, liquid dyes